Integration of electrically activated concrete slab for peak shifting in a light-weight residential building—Determining key parameters. (June 2019) - Olsthoorn, Dave; Haghighat, Fariborz; Moreau, Alain; Joybari, Mahmood Mastani; Robichaud, Miguel
Highlights: Electrically activated thermal storage system can be used for peak shaving of a residential building. A validated model was used to investigate various system configurations and control strategies. Design guidelines for the integration of the system both in terms of its construction and its control have proposed. Abstract: In this study, a thermal storage system for residential buildings in a Northern climate is developed for electrical peak shifting and shaving. To facilitate implementation, only commercially available products are used for the system in conjunction with common construction methods. A thermal model is created within TRNSYS simulation software and validated using data from a two-year monitoring campaign. The thermal model is used to identify key system parameters and propose system design guidelines. It is determined that, for residential buildings with a footprint varying between 80 m 2 to 200 m 2, the basement floor slab can be used for thermal storage with electrical heating cables and that the entire basement heating load can, during the peaks, be shifted to off-peak periods. The best assembly for the basement floor is composed of 102 mm of extruded polystyrene insulation followed by 152 mm of concrete. The electric heating cables are positioned at the bottom of the concrete layer. This assembly can be controlled with the air set point temperature (ASPT). The ASPT of basement rooms during charging needs to be 2 °C higher than the ASPT during normal operating conditions. The required charging time for building footprints of 80, 120 160 and 200 m 2 corresponds to 6.00, 5.51, 5.05 and 4.66 h, respectively. The main achievement of this study is the determination of key parameters for a low cost and easily implementable electrical activation method for concrete slabs to achieve peak shifting.